Neostriatal Neuronal Activity Correlates Better with Movement Kinematics under Certain Rewards - Opris, Ioan; Lebedev, Mikhail A.; Nelson, Randall J. (Frontiers in Neuroscience, 2016)
This study investigated how the activity of neostriatal neurons was related to the kinematics of movement when monkeys performed visually and vibratory cued wrist extensions and flexions. Single-unit recordings of 142/236 neostriatal neurons showed pre-movement activity in a reaction time task with uncertain reward. Monkeys were pseudo-randomly rewarded for correct performance on 75% of trials. A regression model was used to determine the relationship between neostriatal neuronal activity and the kinematic variables (position, velocity and acceleration) of wrist movement, and the dependence of this relationship on reward schedule, sensory cues of different modalities, and movement direction. The regression results were quantified using coefficients of determination (CoD) that represented the proportion of the variance in neuronal activity explained by the regression model. The delay between neuronal firing and wrist movements was quantified as time of best correlation (ToC). The CoD was greater during the trials in which rewards were certain, called “A” trials, as compared with those in which reward was uncertain called (“R”) trials. Additionally, wrist flexion (Flex) trials were characterized by higher CoD as compared to extension (Ext) trials. Finally, CoD was greater during visually (VIS) cued trials than during vibratory (VIB) cued trials. These results are consistent with the hypothesis that reward predictability facilitates the conversion of neostriatal activity into the vigor of wrist movements. We discuss how neostriatal recordings could contribute to building better upper-limb neuroprostheses.